Smart System for Safety of Cyclists - Jamaludin, Muhammad Zulfadhli; Zakaria, Normah; Rubani, Siti Nur Kamariah; Ariffin, Arihasnida; Hamzah, Norhasyimah (Research and Innovation in Technical and Vocational Education and Training, 2022)
In the age of globalization, cycling is more than just a means of transportation, it is also a hobby for all age groups. Cycling trends are increasing in Malaysia as more people own and begin to participate in bicycle groups. Transportation system problems and strict regulatory oversight can lead to traffic jams and accidents. Other means of transportation are one of the causes of accidents on bicycles, especially rear-mounted vehicles. Accidents can also occur because the cyclist is unaware of the current environment. Therefore, the purpose of this study is to design, develop, and test the capabilities of smart system prototypes for cyclist safety. This study used development model of five phases consisting of planning, analysis, design, prototype development and testing. The result of this study is that a prototype of smart system for safety of cyclist can alert users of potential accident and reduce the risk of an accident. Suggestions for improvement are that the entire electrical and electronic circuit needs to be optimized to be more compact and tidier.